Determination of silica aerogels nanostructure characteristics by using small angle neutron scattering technique - Tan, Chier Fang (2006)
Small angle neutron scattering (SANS) technique has been widely employed in probing the microstructure of amorphous materials in the nanometer range (1 to 100 nm). In this study, small angle neutron scattering was used to study the structure of the silica aerogels and titanium containing silica aerogels by using SANS facility at MINT, Malaysia and BATAN, Indonesia. Besides scattering method, imaging technique such as transmission and scanning electron microscopy (TEM and SEM) can be used to provide real-space structure. However, microscopy image may include artifacts and may not be truly representative of the sample. While SANS does not provide real space structure directly, the technique does probe the sample in its entirety. In this work, the aerogels physical properties such as particle size and fractal dimension as a function of pH were studied. In a typical scattering experiment, an incident neutron beam is bombarded to the sample and is elastically scattered. The scattered intensity is measured as a function of the scattering angle which occurs at small angle of less than 100. Reactor was used as our neutron source. The monochromated neutron beam has a wavelength of 0.5 Ã…. The sample which is in powder form is filled into a quartz cell with a 2 mm pathlength. A complete data set consists of three measurements; scattering measured from the sample, scattering from the empty sample holder and scattering from the dark counts due to complete absorber in sample position. The scattered neutrons were detected by a 128 X 128 array area sensitive, gas-filled proportional counter, which is known as Position Sensitive Detector (PSD). A personal computer which is linked to the PSD neutron counting system is used for data collection. SANS neutron counting system programs include the display of scattered neutron data in two and three dimensional isometric view. The resulting 2D scattering pattern is reduced to 1D profile for further analysis. Plots of I(Q) vs Q were derived. Results show that as pH decreases fractal dimension decreases from 3.60 to 2.44. On the other hand, particle size increases from 9.87 nm to 11.26 nm with decreasing pH of the aerogels. Titanium containing silica aerogels has bigger fractal dimension and smaller particle size compared to silica aerogels.